Burden of proof and presumption of innocence in the prosecution of illicit enrichment with reference to the Jordanian legislation - Abu-Morad, Mohannad Ahmad; Ayub, Zainal Amin; Mohd Noor, Fauziah (IISTE, 2016)
It is recognized that the burden of proof in criminal justice is on the shoulder of the prosecution.Likewise, the presumption of innocence is a fundamental principle of human rights concerning fair trials, rights of person to remain silent and principle of innocence until proven guilty beyond reasonable doubts. However, the burden of proof can be shifted from the prosecutor to the defendant in some cases like in cases of money laundering, tax evasion, smuggling, terrorism and illicit enrichment.Hence, this article argues that the right of accused must be balanced against the right of society. This article found that some scholars and in some jurisdictions reject the shifting of onus of proof to the defendant to protect the fundamental provisions of human rights. This article also argues that the burden of proof should be understood as an instrument to curb corruption and deprive corruptors from the proceeds of crimes rather than the exaggeration the presumption of innocence.